2019
DOI: 10.3892/ol.2019.10625
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in exon 8 of TP53 are associated with shorter survival in patients with advanced lung cancer

Abstract: Currently, in clinical settings, all TP53 mutations have been considered equally. However, numerous studies have demonstrated that the position and type of mutation have differential effects on prognosis. Such discrepancy can be partially due to the lack of unifying classification system for TP53 mutations. In the present study, two of the most frequently used systems were compared, according to the location of the mutation or its functional effects on p53 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…These results, in agreement with those reported by Kim et al [7], suggest a negative predictive role of TP53 mutation in all lines of therapy and in relation to all TKIs. Furthermore, our results are consistent with a recent study that found that TP53 mutations in exon 8 are associated with shorter OS of patients receiving a TKI as a first line treatment [27].…”
Section: Discussionsupporting
confidence: 93%
“…These results, in agreement with those reported by Kim et al [7], suggest a negative predictive role of TP53 mutation in all lines of therapy and in relation to all TKIs. Furthermore, our results are consistent with a recent study that found that TP53 mutations in exon 8 are associated with shorter OS of patients receiving a TKI as a first line treatment [27].…”
Section: Discussionsupporting
confidence: 93%
“…Later, we confirmed our results in an independent case series of EGFR-mutated patients (HR for PFS 3.16, 95% CI 1.59-6.28, p = 0.001) [115]. These results were confirmed in a larger case series of NSCLC patients, where TP53 exon 8 mutations were able to predict the prognosis of EGFR-mutated patients, independently of the received treatment [116]. These results were not confirmed by the abovementioned study, which found that TP53 in exon 8 were not predictors for PFS compared with mutations in other exons (13 months vs. 13.1 months, p = 0.2) [112].…”
Section: Tp53 Mutations In Egfr-positive Nsclc: Clinical Significancesupporting
confidence: 86%
“…In addition, 18.3% of the cases tested by NGS carried tumor-mutations in non- EGFR genes classified currently as non-actionable, such as TP53, SMAD4, FBXW7, CTNNB1 and NOTCH1. However, pathogenic variants in these genes were considered to have prognostic or predictive significances for NSCLC patients [ 21 , 22 ]. For the 7.2% of the cases tested by NGS without finding any of tier 1 and tier 2 mutations in neither EGFR nor non -EGFR genes, but we think tier 3 variants (variants of unknown clinical significance-VUS, not reported) found in these cases might represent potentially useful biomarkers for monitoring cancer treatment effects via liquid biopsy.…”
Section: Discussionmentioning
confidence: 99%